2019
DOI: 10.1080/21683603.2019.1689876
|View full text |Cite|
|
Sign up to set email alerts
|

The role of school psychologists in therapeutic interventions: A systematic literature review

Abstract: This systematic literature review establishes evidence for the use of therapeutic interventions delivered by school and educational psychologists in school settings and the extent to which these emulate recent therapeutic practice guidance. Peer-reviewed, empirical studies within the ten-year period 2008-2017 (inclusive) describing recognized targeted and specialist therapeutic interventions were located via systematic searching. Findings revealed that studies included a range of individual and small group the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Nevertheless, studies also indicate the potential for further research in diverse settings, including the school setting, which accounts for 30% (24) of the total. The school setting provides a convenient avenue for accessing therapeutic interventions during school hours, thereby minimizing the disruption to family routines [ 81 ]. Finally, a single intervention (1.25%) conducted in the home of a child with ASD who was not in school was identified [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, studies also indicate the potential for further research in diverse settings, including the school setting, which accounts for 30% (24) of the total. The school setting provides a convenient avenue for accessing therapeutic interventions during school hours, thereby minimizing the disruption to family routines [ 81 ]. Finally, a single intervention (1.25%) conducted in the home of a child with ASD who was not in school was identified [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the diversity of sample sizes, it can be observed that most studies analyze samples of fewer than 100 participants. Conversely, there are instances where the sample size is significantly larger, which could indicate a greater degree of generalizability [ 53 , 81 , 82 ]. An adequate sample size is crucial to ensure the statistical power needed to detect significant differences, thus avoiding erroneous or insufficient conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, we collated papers from scholars all around the globe and on a range of topics directly relevant to the everyday practice of school/educational psychology. Simpson and Atkinson (2021) present us with a systematic literature review of the role of school psychologists in therapeutic interventions. Focusing on the more recent literature, they discuss the need to improve contracting, strengthen effective therapeutic practice, and measure the impact of our work as school psychologists.…”
Section: Goodbye But Not Farewell and Welcome To The Future Of International School/ Educational Psychologymentioning
confidence: 99%
“…Refinement training aims to improve professional leadership by enhancing the communication skills of listening, respect, sincerity and empathy. Teachers learn analytical and consulting skills, define student problems, and provide real-time feedback in the form of recordings, videos, and practical exercises (Simpson & Atkinson, 2021). The roles of observers, supervisors, visitors, and consultants are assigned within the groups.…”
Section: Refinement Trainingmentioning
confidence: 99%